The characteristics and prognosis of patients fulfilling the Appropriateness Evaluation Protocol in a medical admission unit; a prospective observational study - Hallas Jesper; Knudsen Torben; Brabrand Mikkel (BMC, 2011)
Abstract Background To examine the prognostic significance of fulfilling at least one of the Appropriateness Evaluation Protocol (AEP) criteria. Methods Prospective observational cohort study at medical admission units at a regional teaching hospital in Denmark. 3,050 consecutively admitted patients were included, median age 66 (IQR: 50-77), 48% female. We assessed the fulfilment of the AEP criteria and mortality data, length of stay, readmissions and co-morbidity. We analyzed the association between day of admission and time of day and compared the opinion of the admitting doctors and nurses on the relevancy of admission. Results 61.9% of the patients fulfilled the AEP criteria. Patients fulfilling were older (p < 0.001), had a higher in-hospital mortality (p < 0.001), a higher 30-days mortality (p < 0.001), a longer length of stay (p < 0.001), more readmissions within 30 days (p < 0.001) and higher co-morbidity (p < 0.001). There were no association between day of admission and fulfilment of AEP criteria, but significantly fewer patients fulfilled the AEP criteria in the morning hours (p < 0.05). The nurses found 79.1% of the admissions relevant with a sensitivity of 84.8% and a specificity of 30.1% with a Kappa of 0.16. The doctors found 76.2% of the admissions relevant with a sensitivity of 86.4% and a specificity of 40.9% and a Kappa of 0.29. Conclusions Fulfilment of the AEP criteria adequately reflect increased morbidity and mortality of acutely admitted medical patients.